Pengaruh Penambahan Bahan Penunjang Dari Kelapa Sawit PAda Palm Oil Mill Effluent Pada Pembuatan Pupuk Organik Cair - Herman, Dya; Ayusetyowati, Sekar; Mustafa, Mustafa; Rahayu, Ibnu Eka (Journal of Research and Education Chemistry, 2026)
Liquid organic fertilizer comes from fermented animals or plants and is in liquid form. Liquid organic fertilizer can increase soil nutrients because it contains plant nutrients such as phosphorus, nitrogen, and potassium. POME is a liquid waste produced from the manufacture of palm oil from oil palm. Empty Oil Palm Fruit Bunches (OPEFB) and oil palm fronds are sources of organic material rich in nutrients N, P, K, and Mg. This study aims to determine the effect of adding OPEFB ash and oil palm fronds in the manufacture of liquid organic fertilizer using liquid waste from the palm oil industry using MOL OPEFB and fermented for 13 days. In this study, the addition of supporting materials OPEFB ash and oil palm frond fiber with variations of 1%, 3%, 5%, 7% and 9% (w/v). The results showed that the addition of OPEFB ash and oil palm frond fiber was able to increase the content of N, P, and K compared to the initial conditions. The highest nitrogen content was obtained with the addition of 5% oil palm frond fiber, namely 0.1204% (w/v). The highest phosphorus content was obtained with the addition of 9% OPEFB ash, namely 0.0733% (w/v), but both values ​​did not meet the SNI 19-7030-2004 standard. Meanwhile, the highest potassium content was obtained with the addition of 7% OPEFB ash, namely 0.8898% (w/v), which has met the SNI 19-7030-2004 standard. Thus, the addition of OPEFB ash and oil palm frond fiber has an effect on improving the quality of POC, especially in increasing the potassium nutrient content.